PENGOLAHAN PRODUK LOKAL DALAM MENINGKATKAN KEBERDAYAAN MASYARAKAT DI DESA TAWANGSARI KECAMATAN TERAS KABUPATEN BOYOLALI - Eny Hari Widowati; Rachman Djamal (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
This research was conducted in the village Tawangsari Teras Boyolali Regency in September-November 2014 with a survey method, interview and FGD (focused group discutions) as well as qualitative descriptive analysis of the community-based food processing raw agricultural products local to empowerment increase. Results of research addressing community empowerment processors that are affected by factors: a) the level of active participation of the government in empowering; b) human resource capability of facilitators; c) the knowledge and skills of processing; d) processing capital; e) the availability of raw materials; f) institutional / organizational processing; g) the marketing of products; and i) science and technology. Therefore, in order to develop the processing business, especially in the area of ​​research should be conducted by government agencies and the community to improve: a) specific training business management processing of agricultural products ; b) development of business groups similar processed food products ; c) technical assistance efforts since the formulation of the problem to the marketing of products ; d) development utilizing local agricultural production to support business processing ; e) the movement of plant species of plants required in the production of processed food agricultural products; f) the development of the procurement of capital to support the processing group ; g) the development of diversification of processed food products ; h) efforts to facilitate networking equipment supporting and developing partnerships